Developments in the Imaging of Brown Adipose Tissue and its Associations with Muscle, Puberty, and Health in Children - Hu, Houchun H.; Gilsanz, Vicente (Frontiers in Endocrinology, 2011)
Fusion positron emission and computed tomography (PET/CT) remains the gold-standard imaging modality to non-invasively study metabolically active brown adipose tissue (BAT). It has been widely applied to studies in adult cohorts. In contrast, the number of BAT studies in children has been few. This is largely limited by the elevated risk of ionizing radiation and radionuclide tracer usage by PET/CT and the ethical restriction of performing such exams on healthy children. However, metabolically active BAT has a significantly higher prevalence in pediatric patients, according to recent literature. Young cohorts thus represent an ideal population to examine the potential relationships of BAT to muscle development, puberty, disease state, and the accumulation of white adipose tissue. In turn, magnetic resonance imaging (MRI) represents the most promising modality to overcome the limitations of PET/CT. The development of rapid, repeatable MRI techniques to identify and quantify both metabolically active and inactive BAT non-invasively and without the use of exogenous contrast agents or the need for sedation in pediatric patients are critically needed to advance our knowledge of this tissue’s physiology.